Why Love Kills: Power, Gender Dichotomy, and Romantic Femicide. (9th December 2016) - Gregoratto, Federica
Abstract : This article conceptually investigates a type of gender murder, "romantic femicide." I understand this as the extreme form of violence that occurs as a result of men's incapacity to cope with their (female) partners' autonomy and power. The incapacity is not merely an individual pathology but is rather rooted in the dynamic of recognition characterizing love under structural conditions of gender dichotomy. After having sketched out the current discussion about femicide and its shortcomings, I argue for the hypothesis in three steps. First, I draw on a feminist theory of recognition in order to outline a nonviolent form of love. Lovers of this sort would depend on their partners and, at the same time, try to affirm their independence of them. Second, I show how such an interdependence bond would entail a dynamic of mutual empowerment. Third, I argue that love becomes a relation of domination as result of gender dichotomy. The dichotomization of two gender identities, "man" and "woman, " splits the interdependence bond in a way that allows only man's unilateral exercise of power and makes mutual empowerment impossible. Violence might be required for maintaining the dynamic of dominance; finally, romantic femicide may result from the unsustainability of such a structure.